Discovery and SAR of muscarinic receptor subtype 1 (M1) allosteric activators from a molecular libraries high throughput screen. Part 1: 2, 5-Dibenzyl-2H-pyrazolo[4, 3-c]quinolin-3(5H)-ones as positive allosteric modulators. Issue 2 (15th January 2015) - Han, Changho; Chatterjee, Arindam; Noetzel, Meredith J.; Panarese, Joseph D.; Smith, Emery; Chase, Peter; Hodder, Peter; Niswender, Colleen; Jeffrey Conn, P.; Lindsley, Craig W.; Stauffer, Shaun R.
Graphical abstract